Self-management is one of the factors of the professional success of a manager - Ahieieva, Iryna; Plotnichenko, Svitlana; Агєєва, Ірина Вікторівна; Плотніченко, Світлана Романівна (Львів, ЛНУВМБ імені С.З. Ґжицького, 2022)
EN The article reveals the importance of self-management - one of the most important elements of success ful organization and management of modern organizations. The main approaches to the definition of self management by foreign and Ukrainian scientists were studied. We believe that self-management is the use of effective work methods, using resources to achieve goals. Today, a manager is one of the most sought-after professions, which is characterized by professional knowledge of the field of activity and the availability of certain knowledge. The manager's work is useful and meaningful when he has business qualities. A manager must master the science and art of self-management, master the techniques of self-management. The need for self-management in modern conditions as a means of efficiency in achieving the manager's goals is substantiated. For this purpose, the tasks of self-management are defined, which are effective management of one's own life and work activities, successful overcoming of problems, establishing communications with management and colleagues, as well as influencing the work behavior of employees. The relevance of self management for the professional success of a manager is proven. In modern conditions, the activity of a manager is effective if it takes place in conditions of application of all elements of self-management: self governance, self-development, self-control, self-realization, self-analysis, time planning, realization of goals. The role of all elements of self-management in the development of a manager's creative potential is revealed. Thanks to self-management, the manager can realize his abilities, improve himself, thereby con tributing to the development of the enterprise and society. The cited studies show that self-management can be applied by managers of any organizations that have problems in life, activity, career development, defin ing fields of knowledge, contribute to their solution. The theoretical and methodological developments presented in the article are aimed at mastering the technology of self-management by managers, which will allow them to develop, reveal their potential, their opportunities, and become a professional in their field. UK: У статті розкривається значущість самоменеджменту – одного з найважливіших елементів успішної організації та управ ління сучасних організацій. Досліджено основні підходи до визначення самоменеджменту як зарубіжними так і українськими науковцями. Вважаємо, що самоменеджмент – це використання ефективних методів роботи, з використання ресурсів для до сягення цілей. Сьогодні менеджер – це одна з найбільш затребуваних професій, якій характерні професійні знання галузі діяльності та наявність певних знань. Робота менеджера корисна і змістовна тоді, коли він має ділові якості. Менеджер повинен опанувати науку та мистецтво управління самим собою, освоїти прийоми самоменеджменту. Обґрунтовано необхідність застосування самоменеджменту в сучасних умовах, як засобу ефективності в досягненні цілей підприємства, а також менеджера. Для цього визначені завдання самоменеджменту, а це ефективне керування власним життям та трудовою діяльністю, успішне долання проблем, налагодження комунікацій з керівництвом та колегами, а також вплив на трудову поведінку співробітників. Доводиться актуальність самоменеджменту для професійного успіху менеджера. В сучасних умовах діяльність менеджера ефективна, якщо вона відбувається в умовах застосування всіх елементів самоменеджменту: самоврядування, саморозвитку, самоконтролю, само реалізації, самоаналізу, плануванні часу, реалізації цілей. Розкрито роль всіх елементів самоменеджменту в розвитку творчого потенціалу менеджера. Завдяки самоменеджменту, менеджер може реалізувати свої здібності, самовдосконалюватися, тим самим робить свій внесок у розвиток підприємства та суспільства. Наведені дослідження показують, що самоменеджмент мо же бути застосований менеджерами будь-яких організацій, які мають проблеми у житті, діяльності, кар'єрному розвитку, ви значальних галузі знань, сприяють їх вирішенню. Теоретико-методологічні напрацювання, представлені у статті, спрямовані на оволодіння менеджерами технологією самоменеджменту, яка дозволить розвиватися, розкрити свій потенціал, свої можливості, стати професіоналом у своїй справі.
Самоменеджмент – один з факторів професійного успіху менеджера
Keywords: manager; organization; self-management; self-realization; self-development; self-control; self-governance; менеджер; організація; самоменеджмент; саморозвиток; самореалізація; самоврядування